Conceptualizing knowledge transfer as transformation and attunement - Dohn, Nina Bonderup (Frontline Learning Research, 2021)
This article articulates a new theory on the ontology of knowledge transfer. This involves the work of 1) showing that the question “what happens to knowledge in transfer across divergent contexts?” can be made sense of within a situative approach, 2) providing a new conceptualization of situated knowledge, 3) articulating transfer in terms of knowledge transformation and attunement, and 4) putting the issue of learning to transfer knowledge across divergent contexts (back) on the research agenda. The article builds on a view of knowledge as a unity of know-that, know-how, and know-of; which unity forms a practical embodied perspective with which the agent meets the world in interaction. It is argued that knowledge is situatedly realized in attunement to the requirements, possibilities, and restrictions of the concrete situation, as they dynamically unfold. A framework of context levels for analyzing requirements, possibilities, and restrictions (termed “situational characteristics”) is presented. The levels reflect that an activity will always engage with a domain, in a life-setting, taking place within a societal structure, making use of encompassing cultural practices. It is shown how differences in unities of situational characteristics necessitate the transformation of the knowledge perspective in attunement to the situational characteristics of the new context. Towards the end, it is pointed out how this conceptualization of knowledge transfer opens for research into designing and teaching for learning to transfer. Three recent projects are referenced as an illustration of the approach.